Peculiarities of the formation of carbohydrate-amylase complex of Kazakhstan soft wheat grain depending on growing conditions - D. A. Shaimerdenova (Новые технологии)
The processes of the formation of the carbohydrate-amylase complex (CAC) of soft wheat in Kazakhstan depending on natural and climatic conditions of the region, of a precursor have been studied, correlation and regression processing of the data have been carried out. Regression equations describing dependences of CAC indicators on natural and climatic conditions allow predicting the CAC of soft wheat grains depending on the studied factors.